2017
DOI: 10.1163/15685373-12342189
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Tumours and a Fishy Revenge: Evidence for Emotional Content Bias in the Cumulative Recall of Urban Legends

Abstract: This study used urban legends to examine the effects of a cognitive bias for content which evokes higher levels of emotion on cumulative recall. As with previous research into content biases, a linear transmission chain design was used. One-hundred and twenty participants, aged 16–52, were asked to read and then recall urban legends that provoked both high levels and low levels of emotion and were both positively and negatively valenced. The product of this recall was presented to the next participant in a cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 22 publications
0
45
0
Order By: Relevance
“…about peoples' relations and interactions with one another (e.g. Mesoudi, Whiten, & Dunbar, 2006;Stubbersfield, Tehrani, & Flynn, 2015); iii) a bias for emotionally arousing content, such as disgust, or amusement (Eriksson & Coultas, 2014;Stubbersfield, Tehrani, & Flynn, 2017); iv) a bias for minimally-counterintuitive (MCI) information that violates some of our implicit ontological assumptions about the world in ways that makes it more salient than information that can either be taken-for-granted or is incomprehensible (e.g. Barrett & Nyhof, 2001); v) a stereotype-consistency bias, in which information is transformed and recalled in ways that make it more consistent with pre-existing expectations and prejudices (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…about peoples' relations and interactions with one another (e.g. Mesoudi, Whiten, & Dunbar, 2006;Stubbersfield, Tehrani, & Flynn, 2015); iii) a bias for emotionally arousing content, such as disgust, or amusement (Eriksson & Coultas, 2014;Stubbersfield, Tehrani, & Flynn, 2017); iv) a bias for minimally-counterintuitive (MCI) information that violates some of our implicit ontological assumptions about the world in ways that makes it more salient than information that can either be taken-for-granted or is incomprehensible (e.g. Barrett & Nyhof, 2001); v) a stereotype-consistency bias, in which information is transformed and recalled in ways that make it more consistent with pre-existing expectations and prejudices (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…'Content-based' biases describe what kind of information people learn best, owing to its salience or memorability. For example, a bias to transmit emotionally salient content, or negative content, has been found in several laboratory experiments (Bebbington et al 2017;Fessler et al 2014;Stubbersfield et al 2015Stubbersfield et al , 2017. These biases can be compared with unbiased transmission, in which cultural variants are transmitted in equal proportion to their existing frequency in the population.…”
Section: Introductionmentioning
confidence: 99%
“…Memes, which are cultural units of information that may include rumours, tend to propagate further in the social environment when they evoke highly arousing emotions, such as disgust (Heath, Bell, & Sternberg, 2001). Several promising studies that apply the serial reproduction paradigm have demonstrated an emotional content bias in information transmission and transformations (Breithaupt, Li, Liddell, Schille‐Hudson, & Whaley, 2018; Stubbersfield, Tehrani, & Flynn, 2017; Tafani, Marfaing, & Guimelli, 2006). Therefore, the integration of heuristic‐systematic models for the effects of emotional context on information processing of a transmitted message (Chaiken, 1980; Chaiken, Liberman, & Eagly, 1989) appears to be a relevant future direction for rumour research.…”
Section: Limitations Of the Serial Reproduction Paradigmmentioning
confidence: 99%